Crashworthiness performance of the designed concave hexagonal structures as filler element in cylindrical shell in multiple load cases (Fracture and Structural Integrity, 2023)
Safety Impact resistance is defined as the ability of a material to absorb impact energy through controlled failure mechanism. The greater the energy absorption by the crash safety structure, the greater the safety in preventing deformation of the main structure due to impact. In this study, numerical validation, mesh convergence studies and multiple load case studies were performed to investigate crash resistance under axial loading. Numerical validation results show that the similarity between this study and the reference reaches 95%. A deviation of 5% occurs due to different input material properties. The results show that the concave hexagons as filling elements have greater energy absorption capacity than conventional hollow tubes, and the more concave hexagonal structures, the better the energy absorption. Oblique compression was performed in this study and as a result the sample has good impact resistance at low angles and no effect at high angles like 20°.
Keywords: Energy absorption; crashworthiness; thin-walled structures; multi-cell; concave hexagonal